Contemporary problems of the penitentiary rehabilitation and minimizing them - Elżbieta Łuczak (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The study is devoted to the most important problems of the Polish prison system and most often met innovations taken to the purpose of these minimizations of problems. Among the most important problems an overpopulation of penitentiaries was being analyzed, the phenomenon of unemployment of prisoners and disrupting the influence of the leisure time of inmates. Next among others action associated with increasing the residential space was being ranked among most often taken initiatives improving the contemporary penitentiary system (including the use of supervision electronic), with the extension of places of employment and the rise in the remuneration for the work, of implementing methods of the creative social rehabilitation. On account of the fact that these initiatives have more and more universal character from here one should nurse a hope, that contributing to reduce existing penitentiary problems will cause increasing the effectiveness of rehabilitation influences.